Congenital Heart Disease in Adults: Assessment of Functional Capacity Using Cardiopulmonary Exercise Testin - Aguiar Rosa, S (2018)
AIM: The aim of the study was to compare functional capacity in different types of congenital heart disease (CHD), as assessed by cardiopulmonary exercise testing (CPET). METHODS: A retrospective analysis was performed of adult patients with CHD who had undergone CPET in a single tertiary center. Diagnoses were divided into repaired tetralogy of Fallot, transposition of the great arteries (TGA) after Senning or Mustard procedures or congenitally corrected TGA, complex defects, shunts, left heart valve disease and right ventricular outflow tract obstruction. RESULTS: We analyzed 154 CPET cases. There were significant differences between groups, with the lowest peak oxygen consumption (VO2) values seen in patients with cardiac shunts (39% with Eisenmenger physiology) (17.2±7.1ml/kg/min, compared to 26.2±7.0ml/kg/min in tetralogy of Fallot patients; p<0.001), the lowest percentage of predicted peak VO2 in complex heart defects (50.1±13.0%) and the highest minute ventilation/carbon dioxide production slope in cardiac shunts (38.4±13.4). Chronotropism was impaired in patients with complex defects. Eisenmenger syndrome (n=17) was associated with the lowest peak VO2 (16.9±4.8 vs. 23.6±7.8ml/kg/min; p=0.001) and the highest minute ventilation/carbon dioxide production slope (44.8±14.7 vs. 31.0± 8.5; p=0.002). Age, cyanosis, CPET duration, peak systolic blood pressure, time to anaerobic threshold and heart rate at anaerobic threshold were predictors of the combined outcome of all-cause mortality and hospitalization for cardiac cause. CONCLUSION: Across the spectrum of CHD, cardiac shunts (particularly in those with Eisenmenger syndrome) and complex defects were associated with lower functional capacity and attenuated chronotropic response to exercise.